Uncommon metastatic journey: unusual breast metastases of medullary thyroid carcinoma: a case report - Saadallah Fatma; Chrigui Maha; Zemni Ines; Kammoun Salma; Houcin Yoldez; Jbeli Souhail; Driss Maha; Ben Dhiab Tarak (BMC Women's Health)
Abstract Medullary thyroid carcinoma is a neuroendocrine tumor derived from thyroid C-cells. It is a rare aggressive tumor, known to metastasize to lymph nodes, liver, bones, and lungs. We report a case of a young patient with a family history of breast cancer, who developed breast metastases six months post-treatment for medullary thyroid carcinoma. The breast lesion was initially considered benign in ultrasound. Unlike the high prevalence of primary mammary malignancies, metastases to the breast are uncommon, and account for only 0.2–2.7% of all malignancies affecting this organ. This case emphasizes the need for thorough and continuous monitoring of patients with Medullary thyroid carcinoma, even in unusual locations, to ensure early detection and appropriate management. New lesions on imaging should be interpreted with caution to avoid underdiagnosing metastasis. Immunohistochemical analysis confirmed the metastatic origin, underscoring the challenges in distinguishing between primary and secondary breast tumors. This case contributes to the limited literature on MTC breast metastases and advocates for heightened clinical awareness regarding atypical metastatic sites in thyroid cancer patients.